EFFECT OF CYPERMETHRIN INSECTICIDE AGAINST ADULTS OF CULEX QUINQUEFASCIATUS (SAY) - ., ANUKRATI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
Toxicity of cypermethrin against adults of C quinquefasciatus has been studied here within two parameters i. e. lethal time (LT) and lethal concentration (LC) Cypermethrin was found to have a very fast killing effect. On the very low concentration of 54.59 ppm, it kills 50% of population and 221.9 ppm, concentration/kills 90% of mosquito population. These results were verified by the LT50, LT 90 values with a very low 5 ppm conc. of cypermethrin which kills 50% of population within 33 minutes and 90% o population in 40.8 minutes.